2011
DOI: 10.1007/s10067-011-1787-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psoriatic arthritis and moderate–severe psoriasis: analysis of a series of 166 psoriatic arthritis patients selected from a hospital population

Abstract: The aim of the study was to assess the prevalence of moderate to severe psoriasis (MS-P) in patients with psoriatic arthritis (PsA) and the relationship between MS-P and other variables related to arthritis. One hundred sixty-six consecutive patients with PsA periodically monitored at a university hospital's PsA unit in northeastern Spain were included in the study. Patients with psoriasis were classified as having MS-P when systemic treatment for skin was required. Clinical criteria for treatment indication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…In addition, it has been shown that effective systemic therapy may ameliorate cardiovascular risk profiles of psoriatic patients 26,27 . As mentioned previously, psoriatic patients with arthritis were associated with higher PASI scores and higher CRP levels as compared with those without 19,21 . Therefore, methotrexate treatment may reduce the risks for developing severe vascular complications in certain subsets of psoriatic patients with less severe systemic inflammatory status.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, it has been shown that effective systemic therapy may ameliorate cardiovascular risk profiles of psoriatic patients 26,27 . As mentioned previously, psoriatic patients with arthritis were associated with higher PASI scores and higher CRP levels as compared with those without 19,21 . Therefore, methotrexate treatment may reduce the risks for developing severe vascular complications in certain subsets of psoriatic patients with less severe systemic inflammatory status.…”
Section: Discussionmentioning
confidence: 89%
“…26,27 As mentioned previously, psoriatic patients with arthritis were associated with higher PASI scores and higher CRP levels as compared with those without. 19,21 Therefore, methotrexate treatment may reduce the risks for developing severe vascular complications in certain subsets of psoriatic patients with less severe systemic inflammatory status. Our database, however, does not contain information on severity of disease to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although skin involvement is usually mild in patients with PsA, clinicians and patients judge the impact of a PsA treatment by effects on all domains affected by the disease, in particular joints and skin 20–22. Furthermore, achievement of optimal health-related quality of life, the ultimate treatment goal in PsA, requires improvements in both joint and skin manifestations of the disease 1.…”
Section: Discussionmentioning
confidence: 99%
“…To address this point, very recently, a Spanish study showed that, among a group of PsA patients, the subgroup with SpA was significantly associated with moderate to severe psoriasis [13]. Finally, a study aimed to describe differential characteristics of axial involvement in AS compared with that seen in PsA and inflammatory bowel disease (IBD) in a cohort of patients.…”
Section: Introductionmentioning
confidence: 98%